Governance strategies for a successful marine protected area – The case of Torre Guaceto. (May 2020) - Russi, Daniela
Abstract: Marine protected areas (MPAs) are an essential tool for the protection and recovery of marine ecosystems. Most Mediterranean MPAs are multiple-use, i.e., they include a small no-take area and a buffer zone where extractive and non-extractive economic activities are allowed, mostly under restricted conditions. Multiple-use MPAs are characterised by specific governance challenges, which differ from those of no-take ones. They need to find a compromise between conservation goals and the interests of different categories of stakeholders, and in particular the fishery and tourism sectors – whose support and buy-in are essential to ensure compliance. For this reason, it is important to analyse the governance strategy of multiple-use MPAs that are successful both from an environmental and a socio-economic point of view. To contribute to this debate I herein explore the governance strategy of the Torre Guaceto MPA in south-east Italy, a success story that shows how, even in a difficult socio-economic context and with limited public funding, a MPA can lead to the recovery of ecosystems while providing economic benefits to the tourism and fishery sectors. Drawing from a focus group with fishermen and in-depth semi-structured interviews with key stakeholders from the managing Consortium, the tourist and agriculture sectors and two local residents, I argue that the reason for the success of the Torre Guaceto MPA can be found in the use of multiple economic and non-economic incentives, which catalyse synergies among sectors, and in the strong leadership by two local, well-respected, committed and pro-active leaders. Highlights: Combining multiple categories of economic and non-economic incentives is a key feature of successful MPA governance. Well-respected, pro-active and motivated leaders are essential to enable positive change. Synergies among stakeholders can generate conservation and economic benefits in MPAs. Early stakeholder engagement is key to gaining fishermen's support for MPAs and ensuring compliance.